2006
DOI: 10.1097/01.mlg.0000237442.80711.65
|View full text |Cite
|
Sign up to set email alerts
|

Audio‐Vestibular Disturbance in Patients With Behçet's Disease

Abstract: Objective: The present study prospectively investigated the frequencies and characteristics of audiovestibular disturbance and the results of audiologic and vestibular function tests in patients with Behçet's disease. Study Design: A prospective study. Methods: Seventeen patients with Behçet's disease (mean age 41.2 [30 -56] years, 5 males and 12 females), as well as age-and sex-matched healthy controls, were included in this study. All subjects satisfied the diagnostic criteria of the International Study Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Also, vestibular involvement has been reported in 10 to 59% of cases. 9,[21][22][23] Gemignani et al found cochlear hearing impairment in 12 of 20 patients with Behçet disease, and they concluded that the cochlea is involved more frequently than is the vestibular labyrinth. 24 As another indicator of the inner ear involvement, we found no case of sudden hearing loss in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Also, vestibular involvement has been reported in 10 to 59% of cases. 9,[21][22][23] Gemignani et al found cochlear hearing impairment in 12 of 20 patients with Behçet disease, and they concluded that the cochlea is involved more frequently than is the vestibular labyrinth. 24 As another indicator of the inner ear involvement, we found no case of sudden hearing loss in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss has been sporadically described in all of the systemic vasculitides, yet it is most frequently associated with WG with up to 52% of patients having evidence of OM and 8% developing SNHL, 5 whereas patients with CSS have a lower prevalence of otitis (around 10%), but similar rates of SNHL 13 . Although not as well recognized, SNHL in Behçet's disease is reported in 23–55% of patients, suggesting that hearing loss represents the fourth most prevalent clinical symptom after oral and genital ulcers and skin lesions 3,14 …”
Section: Discussionmentioning
confidence: 99%
“…13 Although not as well recognized, SNHL in Behçet's disease is reported in 23-55% of patients, suggesting that hearing loss represents the fourth most prevalent clinical symptom after oral and genital ulcers and skin lesions. 3,14 Less commonly, otologic manifestations form the presenting complaint of patients with systemic vasculitis. Fauci et al, in their report on the long-term follow-up of 85 patients with WG, noted that 25% of patients present with serous OM and 6% with hearing loss as the initial sign of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotologic manifestations have also been reported and cochlear and neural hearing loss are known to be not uncommon. Audio-vestibular disturbance 5) and vestibulo-ocular reflex abnormality have also been reported 16) . In Neuro-Behcet's disease, involvements of intracranial or extracranial arteries or veins have been reported.…”
Section: Clinical Features Of Neuro-behçet's Diseasementioning
confidence: 99%